The temple of culture : assimilation and anti-Semitism in literary Anglo-America - Freedman, Jonathan, 1954- (OUP E-Books., 2000)
Erik Erikson (1902-1994) was one of the most eminent and prolific psychologists of the 20th century. Over his long career he published a dozen books, including classics such as Childhood and Society; Identity, Youth, and Crisis; and Young Man Luther . He was awarded the Pulitzer Prize and the National Book Award in 1970 for his biography Gandhi's Truth. It was also in 1970, when he retired from Harvard University, that Erikson began to rethink his earlier theories of development. He became increasingly occupied with the conflicts and challenges of adulthood--a shift from his earlier writings o.